2022
DOI: 10.5501/wjv.v11.i6.399
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 inhibitors in COVID-19: Beyond glycemic control

Abstract: Coronavirus disease 2019 (COVID-19) is associated with a high risk of mortality and complications in patients with diabetes mellitus. Achieving good glycemic control is very important in diabetic patients to reduce complications and mortality due to COVID-19. Recent studies have shown the mortality benefit and anti-inflammatory effects of Dipeptidyl-peptidase-4 inhibitors (DPP-4i) in diabetic patients with COVID-19. DPP-4i may have a beneficial role in halting the severity of infection primarily by three route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…DPP-4i, which was chosen as a comparator, also has hypothesized immunomodulatory qualities that solicited attention as a potential COVID-19 therapeutic [ 25 ]. Yet, the results of observational studies of DPP-4i-related impact on COVID-19 have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4i, which was chosen as a comparator, also has hypothesized immunomodulatory qualities that solicited attention as a potential COVID-19 therapeutic [ 25 ]. Yet, the results of observational studies of DPP-4i-related impact on COVID-19 have been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Our multivariate regression models showed DPP-4 inhibitors were associated with statistically non-significant decrease in odds for COVID-19 death (OR 0.761; 95% CI 0.568–1.019). Some studies have shown DPP-4 inhibitors mortality benefits in diabetic patients with COVID-19 [ 54 ]. DPP-4 inhibitors might inhibit entry of the virus, inhibit inflammation and fibrosis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown DPP-4 inhibitors mortality benefits in diabetic patients with COVID-19 [ 54 ]. DPP-4 inhibitors might inhibit entry of the virus, inhibit inflammation and fibrosis [ 54 ]. However, several studies have shown negative associations in terms of increased mortality risk and intensive care unit (ICU) admission risk for people who use them [ 27 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there have been studies that found otherwise and showed no beneficial effects of DPP-IV blockade [57,58]. Recent evidence suggests that DPP-IV and its inhibitors play a role in the pathogenesis of severe COVID-19 [59,60]. Nevertheless, this area requires further research to elucidate its exact role in mediating severe manifestation of the disease, especially when clinical trials investigating DPP-IV inhibitors in the COVID-19 management provide conflicting results.…”
Section: Discussionmentioning
confidence: 99%